Digestibility and Nutrient Utilization of Some Agro-Industrial By-Products Fed to Growing Pigs in the Humid Tropics - Amaefule, K.U.; Abasiekong, S.F.; Ibe, S.N.; Onwudike, O.C. (Pakistan Journal of Nutrition, 2009)
Digestibility and nutrient utilization of some agro-industrial by-products fed to growing pigs in the humid tropics were determined with twelve castrated male hybrid (Large White x Landrace) pigs whose weights ranged from 15.33 to 17.67 kg (average 16.17 kg) and aged 13 weeks. The experimental design was a Completely Randomized Design (CRD). Each of the four treatments had three replicates and a castrated male per replicate. Locally constructed metabolism cages (107 cm x 60 cm x 50 cm) were used in the experiment. Parameters measured were nutrient intake, digestibility coefficients of DM, CP, CF, Ether Extract and Nitrogen Free Extract (NFE). Others were energy utilization, nitrogen (N) balance and protein utilization. Wheat offal fed to growing pigs significantly (P<0.05) increased DM (418 g) and organic matter (391 g) intakes but significantly depressed apparent digestibility coefficient of ether extract (67.50%) and nitrogen intake (16.00 g). Other nutrient and energy utilization indices were not significantly (P>0.05) affected. The conclusion was that Palm Kernel Meal (PKM), Brewers Dried Grain (BDG), wheat offal or equal proportions of PKM+BDG fed to growing pigs have similar apparent nutrient digestibility coefficients, energy utilization, nitrogen balance and protein utilization. However, wheat offal could decrease digestibility coefficient of Ether Extract (EE) and also nitrogen intake.